PERANCANGAN SISTEM PENGINPUTAN DAN PENYIMPANAN ARSIP DIGITAL DATA JAMAAH UMROH BERBASIS MICROSOFT ACCESS PADA PT DAKWAH NADA WISATA (DNW TOUR) - Izzatunnisa, Nazwa; Purwati, Purwati; Sunanto, Sunanto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to develop a digital archiving system for managing umrah pilgrims’ data at PT Dakwah Nada Wisata (DNW Tour), utilizing Microsoft Access as the development platform. The study employs a Research and Development (R&D) approach, guided by the ADDIE model comprising Analysis, Design, Development, Implementation, and Evaluation phases. The system is designed to facilitate data entry for pilgrims, registration, payments, departure schedules, automated reporting, and integrated data retrieval. The implementation results indicate that the system is effectively operable by administrative personnel and serves as a reliable replacement for the previously used manual archiving method. Empirical testing reveals a substantial improvement in data retrieval efficiency, reducing the average search time from 3–4 minutes to under one minute. The availability of a user manual further enhances the system’s usability, enabling staff to operate it independently. Overall, the developed digital archiving system significantly improves data organization and accuracy, thereby strengthening administrative processes at DNW Tour.